Microfluidic-LAMP chip for the point-of-care detection of gene-deleted and wild-type African swine fever viruses and other four swine pathogens - Ji, Chihai; Zhou, Ling; Chen, Yonghui; Fang, Xueen; Liu, Yanhong; Du, Mengkan; Lu, Xiandong; Li, Qianniu; Wang, Heng; Sun, Yuan; Lan, Tian; Ma, Jingyun (Frontiers in Veterinary Science, 2023)
Different pathogens causing mixed infection are now threatening the pig industry in the context of the African Swine Fever (ASF) circulating especially in China, and it is crucial to achieving the early diagnosis of these pathogens for disease control and prevention. Here we report the development of a rapid, portable, sensitive, high-throughput and accurate microfluidic-LAMP chip detection system for simultaneous detection and differentiation of gene-deleted type and wild-type African swine fever virus (ASFV), pseudorabie virus (PRV), porcine parvovirus (PPV), porcine circovirus type 2 (PCV2) and porcine reproductive and respiratory syndrome (PRRSV). The newly developed system was shown to be sensitive with detection limits of 101 copies/μL for ASFV-MGF505-2R/P72, PPV and PCV2, 102 copies/μL for ASFV-CD2v, PRV and PRRSV. The system was highly specific (100%) and stable (C.V.s<5%) in its ability to detect different pathogens. A total 213 clinical samples and 15 ASFV nucleic acid samples were collected to assess the performance of the detection system, showing highly effective diagnosis. Altogether, the developed microfluidic-LAMP chip system provides a rapid, sensitive, high-throughput and portable diagnostic tool for the accurate detection of multiple swine pathogens.